From emergency department to operating room: interventional analgesia techniques for hip fractures. Issue 5 (October 2021) - Garip, Levin; Balocco, Angela L.; Van Boxstael, Sam
Abstract : Purpose of review: To provide an update on pain management options with regional anesthesia for patients with hip fractures at the emergency department (ED). Recent findings: Patients who sustain a hip fracture are typically admitted and diagnosed in the ED before being transferred to the operating room for surgery. Studies have clearly demonstrated the ability of the fascia iliaca compartment blocks (FICBs) and femoral nerve blocks (FNBs) to reduce pain and the risk of an acute confusional state. Their administration at an early stage of the patient's trajectory in the ED is beneficial. Recent anatomical studies contributed new knowledge of nociception in the hip joint, which allowed the development of more specific infiltration analgesia techniques without muscle weakness (e.g., pericapsular hip blocks). Further research on the timing of nerve blocks and an evaluation of new motor sparing techniques is indicated. Summary: FICB and FNB are established and recommended techniques in pain management for hip fracture patients. Their use early on in the ED may improve patient comfort and outcome. Pericapsular nerve hip blocks could provide a relevant alternative in future pain management in this group of patients.